Association of Biochemical & Anthropometric parameters with depressive disorder among adults in a Health care centre - Tayyaba Batool, Muhammad Amin Khan, Syed Ahmed Mahmud, Qurat-Ul-Ain, Anam Rehman, Naeem Amjad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Depression may be a common psychiatric disorder. In spite of the fact that numerous risk factors for sadness have been reported, the affiliations of biochemical and anthropometric records with depressive disorder remain unclear. Depressive disorder is a leading cause of illness around the world. Aim: To access the association between biochemical and anthropometric parameters with depressive disorders among adults Methods: This quantitative cross sectional study was conducted at B.V. Hospital, Bahawalpur from July 1, 2022 to December 31, 2022. A pre validated questionnaire was used. Study was carried out at outdoor patient department of Bahawal Victoria Hospital Bahawalpur. The total numbers of patients were 250 who participated after taking the informed consent. The study was done by simple random sampling technique. Detailed information was given to patient about the current research. Results: The descriptive statistics for anthropometric measures, demographic, baseline variables and CES-D scores for all the subjects are summarized in Table 1. Total number of participants in the study was 250 in which 115 were males and 135 were females. Baseline characteristics were measured include weight, waist circumference and body mass index and others parameters include systolic and diastolic BP, blood sugar fasting, glycemic control and lipid profile was measured both in depressed and not depressed group. Conclusion: Depression and obesity are major wellbeing issues worldwide and may increase metabolic disorders. Obesity, which is related with numerous wellbeing issues related to changes in way of life, can take after depression that happened earlier in life or in early adulthood, a vital time for implementation of health-promoting interventions. Keywords: Depression, Biochemical parameters, Anxiety, Adults, Health Care